# math

posted by .

Solve the equation algebraically. Round the result to three decimal places.

log4 x - log4(x-1) = 1/2

• math -

remember log a- log b= log(a/b)

so with that..
log4 (x/(x-1))=1/2
x/(x-1)= 16
then solve for x.

• math -

Greetings:

log_4[x] - log_4[x-1] = 1/2 implies log_4[x/(x-1)] = 1/2 which means that 4^(1/2) = x/(x-1) or, 2 = x/(x-1). I shall assume you can finish from there.

Regards,

Rich B.

## Similar Questions

1. ### Algebra II

Please check the following: Solve log4(m-3)+ log4(m+3) =2 Answer: 1 Solve 6^3n=43^5n-4 Answer: 1.1202 Solve 5^2x+1>=50 Answer:x>=4.5000 Use common logarithms to approximate log9(207) to four decimal places. Answer: 2.4270 Ealuate: …
2. ### Algebra II

Solve, round to four decimal places if necessary: log4(x-9)=2 Answer: x-9=4^2 x-9=16 x=11 log4(z)+log4(z-3)=1 Answer: z+z-3=1 2z=4 z=2 Thanks for checking my work.
3. ### Logarithms

Solve log4 x + log4(x-2)=log4(15) I know how do the example in my book but I don't know what I'm doing wrong here. log4 x + log4(x-2)=log4(15) log4 [x + log4(x-2)]=log4(15) (x^2 + x)=4 x^2 + x-4=0
4. ### Algebra 2

Simplify: 1. 2log10^5+log10^4 2. 2log3^6-log3^4 3. log4^40-log4^5 4. log4^3-log4^48 I need to see all of the steps. Thanks
5. ### Math

Evaluate the expression without using a calculator: log4(2)= ____?

solve for x: log4 X - log4 2 = 2 log(2x) = 2 Now what do I do?
7. ### Math

solve for x: log4 X - log4 2 = 2 log(2x) = 2 Now what do I do?
8. ### Trig/Pre-Calc

Could someone please help me on this problem. I'm really confused, and this assignment is due tomorrow. Solve the logarithmic equation algebraically. Approximate the result to three decimal places. log4x-log4(x-1)=1/2 To start off …
9. ### Math Algebra 2

#4. Express the logarithm in terms of log2M and log2N: log2 1/MN #5. Simplify: log4 3 - log4 48 #6. Solve the equation: loga x = 3/2loga 9 + loga 2 #7. Solve the equation: logb (x2 + 7) = 2/3logb 64 #8. Solve the equation: loga (3x …
10. ### algebra

Solve the equation algebraically. Round the result to three decimal places. Verify your answer using a graphing utility. e−^8x − 6xe^−8x = 0 x = I need help solving this problem.

More Similar Questions